Chemical treatment of asphalt with sulfur sludge using microwave radiation - Wafaa Al-Aragi (College of Education for Pure Sciences, 2005)
Chemical modification of asphalt had been used to modify the rheological properties by treatment with sulphur at different experimental conditions. The modification achieved by using application of microwaves (microwave oven), A comparison between the properties of modified asphalt and original ones was made through the following tests: softening point, penetration, ductility and A suitable asphalt happened at first treatment including low range of microwaves spectroscopy and low time (5 min), this is explain in PI = 1,94,